Association between serum albumin-to-creatinine ratio and clinical outcomes among patients with ST-elevation myocardial infarction after percutaneous coronary intervention: a secondary analysis based on Dryad databases - Huang, Xiaoye; Liu, Yuchun; Zhong, Chuyang; Lin, Zengrui; Zheng, Binyun (Frontiers in Cardiovascular Medicine, 2023)
Background The prognostic value of the serum albumin-to-creatinine ratio (sACR) in patients with ST-elevation myocardial infarction (STEMI) remains unclear. This study aims to investigate the impact of the sACR on incident major adverse cardiovascular events (MACEs) among revascularized patients with STEMI at long-term follow-up. Methods A total of 461 patients with STEMI who underwent successful primary percutaneous coronary intervention (PCI) were enrolled to explore the association between the sACR and MACE during a 30-month follow-up. The Cox regression proportional hazard model was used to evaluate the prognostic value of the sACR. Heterogeneity among specific groups was investigated by subgroup analysis. Results A total of 118 patients developed MACE during the follow-up. A negative association between the sACR and MACE was found after adjusting for other MACE-related risk factors. In subgroup analyses, the sACR was inversely associated with MACE in patients aged ≥ 60 years [hazard ratio (HR), 0.478; 95% confidence interval (CI), 0.292–0.784], male (HR, 0.528; 95% CI, 0.327–0.851), with hypertension history (HR, 0.470; 95% CI, 0.271–0.816), and with anterior wall myocardial infarction (HR, 0.418; 95% CI, 0.239–0.730). Meanwhile, the negative association between the sACR and MACE remained significant in a sensitivity analysis that excluded patients with low serum albumin levels (HR, 0.553; 95% CI, 0.356–0.860). Conclusions Patients with STEMI who underwent successful PCI with a low sACR had a higher risk of developing MACE, indicating that the sACR could be used to identify patients with STEMI who are at high risk of developing MACE.